2013
DOI: 10.3389/fonc.2013.00102
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model of the Role of VEGF Binding in Endothelial Cell Migration and Capillary Formation

Abstract: Vascular endothelial growth factor (VEGF) is the most studied family of soluble, secreted mediators of endothelial cell migration, survival, and proliferation. VEGF exerts its function by binding to specific tyrosine kinase receptors on the cell surface and transducing the effect through downstream signaling. In order to study the influence of VEGF binding on endothelial cell motion, we develop a hybrid model of VEGF-induced angiogenesis, based on the theory of reinforced random walks. The model includes the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…It has been reported that VEGF and IL-8 can promote endothelial cell migration in an autocrine manner [15, 16]. In our system, cell migration rate of HUVECs was accelerated after CM treatment compared with that of the control.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that VEGF and IL-8 can promote endothelial cell migration in an autocrine manner [15, 16]. In our system, cell migration rate of HUVECs was accelerated after CM treatment compared with that of the control.…”
Section: Discussionsupporting
confidence: 54%
“…VEGF and IL-8 secreted by cancer cells act as chemoattractants in promoting motility of endothelial cell during tumor angiogenesis [12-14]. It is noteworthy that VEGF and IL-8 are secreted not only by tumor cells, but also by endothelial cells, thereby enhancing endothelial cell migration and angiogenesis [15, 16] . However, the molecular mechanisms underlying the effect of autocrine VEGF and IL-8 on endothelial cell migration are not completely understood to date.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hybrid models proposed to map VEGF-depended angiogenesis consider that VEGF concentration changes in addition to modeling che-motaxis of endothelial cells using the reinforced random walk. For example, it is reported that the hybrid model was able to predict the threshold concentration required to stimulate the quiet cells for a biased motion, as well as the optimum concentration for their movement [83].…”
Section: Reinforced Random Walkmentioning
confidence: 99%
“…Using all of these assays, enamel matrix derivative was found to possess pro‐angiogenesis properties . These assays were used to test other growth factors, such as vascular endothelial growth factor, epidermal growth factor, fibroblast growth factor and platelet‐derived growth factor . Alternatively, enamel matrix derivative could promote angiogenesis by inducing the expression of pro‐angiogenesis molecules, such as vascular endothelial growth factor, in different cells and this was demonstrated in gingival fibroblasts and periodontal ligament cells .…”
Section: In Vitro Models Of Soft‐tissue Wound Healingmentioning
confidence: 99%